Biodegradation of phenol by locally isolated Acinetobacter sp. strain AQ5NOL 1 and purification of phenol hydroxylase - Ahmad, Siti Aqlima (2011)
Phenol and its derivatives are categorized as one of the most toxic compounds. Phenolic compounds are ubiquitous pollutants which mainly originate from industrial processes such as resin manufacturing, pharmaceutical, petrochemical, oil refinery,plastic and textile industries. These pollutants are persistent in nature and are considered highly hazardous due to their toxicity, mutagenicity and carcinogenicity towards most biological processes even at low concentrations. At present, the bioremediation technique involving microorganisms such as bacteria, fungi and yeast has been the target of phenol remediation technologies. However, the growth of these microorganisms is inhibited at high concentrations of phenol, thus limiting the efficiency of the biodegradation. The efficiency of phenol biodegradation can be enhanced by a process of cell immobilisation. Accordingly, the aim of this study was to seek potential phenol-degrading bacteria from local bacterial strains. The study encompasses the process of screening, isolating, identifying and characterizing phenol-degrading bacteria. The effects of phenol concentration, heavy metals,pesticides and respiratory inhibitors on the efficiency of phenol biodegradation by freely suspended and immobilised cells are also compared. This is then followed by purification and characterization of the phenol-degrading enzyme. From the 115 samples collected from different locations, 37 pure phenol-degrading bacteria were isolated of which 6 were able to degrade 100% 500 mg/L phenol. From the 6 isolates, bacterial Isolate number SA28s(i) isolated from Hutan Simpan Gunung Johor, has the best capability to degrade phenol in a mineral salt medium, pH 7.5 at 30°C, after 4 days of incubation compared with the other isolates. Isolate SA28a(i) was identified as Gram-negative cocci. 16s rRNA analysis placed this isolate in the Acinetobacter genera but did not match any known species in the NCBI database. Thus, it is tentatively named it as Acinetobacter sp. strain AQ5NOL 1 using molecular phylogenetics analysis of the sequenced 16s rRNA gene. Studies were carried out to optimise the degradation of phenol and bacterial growth by free and immobilised cells in gellan gum. The combination of 0.04% (w/v) ammonium sulphate and 0.01% (w/v) of NaCl at pH 7 (phosphate buffer) gave optimum degradation of phenol and bacterial growth by the free cells. The combination of 0.75% (v/w) gellan gum, 300 beads, and bead size of 3 mm gave optimum phenol degradation by the immobilised cells. Acinetobacter sp. strain AQ5NOL 1 immobilised in gellan gum beads showed enhanced degradation of elevated concentrations of phenol (1900 mg/L) compared to the free cells (1100 mg/L) and could be reused for at least 45 cycles. Heavy metals, pesticides and respiratory inhibitors showed less inhibition of phenol degradation in immobilised cells than the free cells. Purification and characterisation of the phenol degrading enzyme known as phenol hydroxylase was conducted with anion exchange chromatography using DEAE-Sepharose®, DEAE–Sephadex®, Q-Sepharose® and gel filtration chromatography using gel filtration of Agilent ZorbaxTM (GF-250). One band was visualised on the gel filtration fraction at 50 kDa using the SDS polyacrylamide-gel electrophoresis (SDS-PAGE) and native polyacrylamide-gel electrophoresis (Native-PAGE), suggesting that the enzyme preparation is homogenous. In the enzyme kinetic studies, the Km and Vmax obtained for phenol were 13.4 μM and 2.5 μmole/min/mg protein (Michaelis-Menten); 17.57 μM and 2.89 μmole/min/mg protein (Lineweaver-Burk) respectively. The Km and Vmax obtained for NADH were 84 μM and 2.31 μmole/min/mg protein (Michaelis-Menten); 50.7948 μM and 1.724 μmole/min/mg protein (Lineweaver-Burk) respectively. Phenol degradation by phenol hydroxylase was optimum at pH between 6.5-7.5 by phosphate buffer and 7-7.5 by Tris-HCl buffer at 15-25°C. The enzyme was stable at –20°C for 40 days in phosphate buffer at pH 7.5. The outcome of this study on phenol degrading bacteria and enzyme will contribute to additional knowledge on a new source of more efficient microbe in phenol degrading process, hence contributing to environmental sustainability especially for a developing country like Malaysia.